2015
DOI: 10.1021/tx5005198
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole Inhibits Pancreatic Cancer Cell Invasion through a Nongenomic Aryl Hydrocarbon Receptor Pathway

Abstract: Omeprazole and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) are aryl hydrocarbon receptor (AhR) agonist that inhibit invasion of breast cancer cell through inhibition of CXCR4 transcription. Treatment of highly invasive Panc1 pancreatic cancer cells with TCDD, omeprazole and seven other AhR-active pharmaceuticals showed that only omeprazole and tranilast but not TCDD inhibited invasion in a Boyden chamber assay. Similar results were observed in MiaPaCa2 cells, another quasimensenchymal pancreatic ductal adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 47 publications
7
59
0
Order By: Relevance
“…Differential AhR expression has been observed in tumor vs. normal tissues for multiple tumors, and the levels and prognostic significance of the AhR are tumor-specific [26–37]. For example, a recent survey of tumor array database showed that AhR mRNA expression in breast, lung, prostate and cervical cancers was similar to non-tumor tissue, whereas expression was higher in stomach, thyroid, colon and pancreatic tumors compared to non-tumor tissue [34]. Moreover, high expression of the AhR in pancreatic tumors was a prognostic factor for increased patient survival [34].…”
Section: Role Of the Ahr In Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Differential AhR expression has been observed in tumor vs. normal tissues for multiple tumors, and the levels and prognostic significance of the AhR are tumor-specific [26–37]. For example, a recent survey of tumor array database showed that AhR mRNA expression in breast, lung, prostate and cervical cancers was similar to non-tumor tissue, whereas expression was higher in stomach, thyroid, colon and pancreatic tumors compared to non-tumor tissue [34]. Moreover, high expression of the AhR in pancreatic tumors was a prognostic factor for increased patient survival [34].…”
Section: Role Of the Ahr In Carcinogenesismentioning
confidence: 99%
“…For example, a recent survey of tumor array database showed that AhR mRNA expression in breast, lung, prostate and cervical cancers was similar to non-tumor tissue, whereas expression was higher in stomach, thyroid, colon and pancreatic tumors compared to non-tumor tissue [34]. Moreover, high expression of the AhR in pancreatic tumors was a prognostic factor for increased patient survival [34]. In contrast, high expression of the nuclear AhR was a negative prognostic factor for urothelial cancer patients [30].…”
Section: Role Of the Ahr In Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, internalization of CXCR4 does not occur. Instead, the receptor is inhibited at the transcriptional level [52]. Because of this, the results of ongoing clinical trials evaluating the effects of CQ and HCQ will play a pivotal role in the validation or withdrawal of preclinical findings.…”
Section: Controversies and Future Perspectivesmentioning
confidence: 99%
“…Additionally, and in contrast to concerns about carcinogenicity, several of these drugs have been shown to suppress the growth, invasion, and/or metastases of experimental cancers in an AhR dependent manner [3741]. Taken together, these findings provide further evidence that TCDD should not set the precedent for the selective discrimination against the development of RMAhRLs.…”
Section: Evidence That Ahr Ligands Are Not Inherently Riskymentioning
confidence: 97%